Nitrogen Doped Graphene Basal Nanocarbon Materials for Catalytic Decomposition of Persistent Organic Pollutants - Kang, Jian (Curtin University, 2019)
Advanced oxidation processes have been extensively studied for wastewater purification in past years. Nanocarbons demonstrated robust catalytic activity in activation of sulfate oxidants for toxic organics degradation, meanwhile; completely avoiding the secondary contamination. This research was dedicated to the investigation on the relationship between the structure modification of nanocarbon materials and the catalytic activity and stability. The findings provided a novel and feasible way to address global water pollution issues.